Colour science in the examination of museum objects : nondestructive procedures - Johnston-Feller, Ruth (Los Angeles: Getty Conservation Institute, 2001)
A comprehensive discussion of non-destructive spectrophotometric tools and techniques used during the technical examination of works of art in order to analyze the colour and appearance of materials. Topics include spectrophotometry, colorimetry, colorant mixtures, analytical techniques, reflection, fluorescence, and the effects of extenders, fillers and inserts.
Includes bibliographical references (p. [328]-350) and index.
Keywords: Colorimetry; Art $1 (BConservations; Spectrophotometry; Conservation, restoration & care of artworks -- Museums & museology -- Scientific equipment & techniques -- Scientific equipment & techniques; laboratory equipment; ART / Color Theory; Art -- Techniques; Art -- History; Art objects -- Conservation and restoration -- Color in art -- Spectrophotometry